1978
DOI: 10.1104/pp.62.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Photolability of Photosynthesis in Two Separate Mutants of Scenedesmus obliquus

Abstract: Two separate mutants of the green alga, Senedesus oblquus, are described in which photosynthesis is sensitive to moderate intensities of white light (100 mw cm-'). Heterobtphic cultures of both mutants lose photosynthetic activity when exposed to white lght, the site of at least the initidal phase of this inactivation is within photosystem I. Although al whole cell and cell-free reactios typical of photosystem I exam_ied are hibited by irradiaton, the pincipal com nt of photosystem I affected is P-700. In l1gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In addition, it was observed that the photoinhibition of P700 activity was closely correlated with the changes in ~bp (Tables 6 and 8). Previous in vitro studies of isolated thylakoid membranes and microalgae (Harvey and Bishop 1978, Gerber and Burris 1981, Satoh and Fork 1982 have also related photoinhibition to a selective loss of active P700. In contrast, chilling potato leaves in light did not induce or enhance photodamage of the PS II function (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it was observed that the photoinhibition of P700 activity was closely correlated with the changes in ~bp (Tables 6 and 8). Previous in vitro studies of isolated thylakoid membranes and microalgae (Harvey and Bishop 1978, Gerber and Burris 1981, Satoh and Fork 1982 have also related photoinhibition to a selective loss of active P700. In contrast, chilling potato leaves in light did not induce or enhance photodamage of the PS II function (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Until recently, PSII has been generally thought to be the primary target for photoinhibition although photoinactivation of PSI was also reported in in vitro systems [5–7]. Since the initial reports on PSI photoinhibition in vivo in algal systems [8, 9]and intact spinach leaves [10], there have been several additional reports of selective inhibition of PSI related photochemical activities under either weak illumination in chilling sensitive plants [11–13]or under high light in potato leaves [14]. In these reports, it was demonstrated that during light stress at low temperatures the maximum quantum yield of electron transport through PSI, the pool of photooxidizeable reaction center pigment of PSI (P700), and the efficiency of P700 oxidation were dramatically reduced [11–14].…”
Section: Introductionmentioning
confidence: 99%
“…The Photosystem I activity measured here (P700 photo-oxidation in Triton-solubilized membranes) is independent of noncyclic electron flow and Photosystem I1 activity. Losses in P700 activity have also been observed in response to photoinhibitory light levels in a benthic diatom (Gerber & Burris 1981) and the green algae Scenedesmus obliquus (Harvey & Bishop 1978) and Dunaliella tertiolecta (Falkowski 1984).…”
Section: Discussionmentioning
confidence: 96%